2021
DOI: 10.1097/mol.0000000000000814
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysfunction-associated fatty liver disease: advances in genetic and epigenetic implications

Abstract: Purpose of reviewFatty liver associated with metabolic dysfunction, also known under the acronym NAFLD (nonalcoholic fatty liver disease) is the leading global cause of chronic liver disease. In this review, we address the state of research on genetics and epigenetics of NAFLD with focus on key discoveries and conceptual advances over the past 2 years. Recent findingsThe analysis of NAFLD-associated genetic variant effects on the whole-transcriptome, including quantitative trait loci (QTL) associated with gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…9 But not only the clinical phenotype of NAFLD but also substantial knowledge from the past years regarding genetic associations has supported the metabolic nature of this disease. 10 In addition, pathophysiologic insights strongly support the importance of…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…9 But not only the clinical phenotype of NAFLD but also substantial knowledge from the past years regarding genetic associations has supported the metabolic nature of this disease. 10 In addition, pathophysiologic insights strongly support the importance of…”
Section: Introductionmentioning
confidence: 96%
“… 9 But not only the clinical phenotype of NAFLD but also substantial knowledge from the past years regarding genetic associations has supported the metabolic nature of this disease. 10 In addition, pathophysiologic insights strongly support the importance of metabolic pathways that trigger in many affected NAFLD subjects liver inflammation, fibrosis and immunological processes. 11 Furthermore, caloric excess as common basis of this disease affects the gut microbiome that is frequently disturbed potentially contributing to disease pathogenesis.…”
Section: Introductionmentioning
confidence: 96%
“…However, a great deal of the heritability make-up remains unknown [53]. Several studies have indicated that this missing background is the interaction of genetic, epigenetic and environmental risk factors [54 ▪▪ ,55 ▪ ]. In this context, genetic risk-allele scores (GRSs) are one of the most common approaches to assess the cumulative effect of many genetic factors with a small effect, with or without nongenetic clinical factors with input for treatment presumption [56].…”
Section: Introductionmentioning
confidence: 99%
“…Genomics has enabled the identification of genetic variants that confer either risk or protection against steatotic liver diseases and fibrosis [ 1 ]. Epigenetics/epigenomics has helped to clarify the relationship between MASLD and comorbidities [ 2 ], disease severity [ 3 ], and even the interaction with the microbiome, as recently described [ 4 ]. Besides, liver transcriptomics have revealed the key mechanisms regulating gene expression in the context of MASLD and MASH [ 5 ].…”
mentioning
confidence: 99%